Time Trends of Acrylamide Exposure in Europe: Combined Analysis of Published Reports and Current HBM4EU Studies - Poteser, Michael (2022)
This article belongs to the Special Issue Analysis of Human Biomonitoring Data and Risk Assessment of Human Exposure to Environmental Chemicals: What Do We Learn for Prevention?